Comparative analysis of financial performance in the tourism industry before and during the COVID-19 virus outbreak - Subing, Hesty Juni Tambuati; Nugroho, Randhy; Lapae, Kanaya (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2024)
This research seeks to conduct a comparative analysis of the financial performance among companies within the tourism industry sector, restaurants, and hotels listed on the IDX as measured by financial ratios (CR, DER, ROE, TATO) and Stock Price. Employing a quantitative research approach, the study utilized secondary data collected from quarterly financial reports spanning from 2018 to the quarter of 2021. The sampling method was purposive, with seven companies included in the study. The normality test was conducted using the Kolmogorov-Smirnov method; it was determined that the dataset did not exhibit a normal distribution, so the non-parametric Wilcoxon signed-rank test was used. The study's findings indicate that the CR and DER did not exhibit significant differences before and during the Covid-19 virus outbreak. Conversely, ROE, TATO, and Stock Prices demonstrated notable differences before and during the Covid-19.